2012
DOI: 10.1177/1473325012470694
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in a cultural context: Taiwanese female earthquake survivors

Abstract: The aim of the current study was to examine how females survive natural disaster in non-western culture and to gain understanding of their unique experiences in rebuilding their lives. In September 1999, a major earthquake, named '921 Earthquake,' measuring 7.3 on the Richter Scale occurred in Taiwan. Many people survived, struggling a great deal in their efforts to reconstruct their lives. Five years after this earthquake, many survivors, including women, were reported to have rebuilt self-sufficient lives. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…I decided to focus only on women because traumatic birth is specific to women and I believe these studies closely match the clinical sample in this study. For example, a qualitative study conducted by Liu and Mishna (2014) investigated resilience in the cultural context of Taiwanese female earthquake survivors. They found that the women used coping strategies influenced by female gender roles in the family, which includedputting their children as a first priority in their role as a mother, accepting the role of working within the home while the men were the providers, and taking over this role when the men were not able to provide.…”
Section: Resilience and Traumatic Childbirthmentioning
confidence: 99%
“…I decided to focus only on women because traumatic birth is specific to women and I believe these studies closely match the clinical sample in this study. For example, a qualitative study conducted by Liu and Mishna (2014) investigated resilience in the cultural context of Taiwanese female earthquake survivors. They found that the women used coping strategies influenced by female gender roles in the family, which includedputting their children as a first priority in their role as a mother, accepting the role of working within the home while the men were the providers, and taking over this role when the men were not able to provide.…”
Section: Resilience and Traumatic Childbirthmentioning
confidence: 99%
“…Seven articles examine mediating factors that reduce the negative impacts of disaster events on people: (1) four identify social connectedness as a mediator (Drolet et al, 2018, Hawkins and Maurer, 2010, Liu and Mishna, 2014, Marlowe, 2015; (2) another three identified higher socioeconomic status as a mediator (Kulkarni et al, 2008, Alipour et al, 2015, Pentaraki, 2013; (3) three comment on reconstruction and recovery policies and responses as mediators (Kulkarni et al, 2008, Pentaraki, 2013, Alipour et al, 2015; and (4) one highlights the mediating effect of the degree of exposure to the disaster (Kreuger and Stretch, 2003).…”
Section: The Effects Of Disasters On People and Mediators Of These Efmentioning
confidence: 99%
“…For example, following Hurricane Katrina in the US, people used connections and close ties for immediate support (that is, bonding social capital), and bridging and linking social capital to revitalise their communities (Hawkins & Maurer, 2010). Thus, it is important for social workers to build community capacity by harnessing social capital, while also recognising, where appropriate, the value of cultural norms in promoting resiliency (Liu & Mishna, 2014). Further, recovery and reconstruction policies that exacerbate socioeconomic and structural inequalities can mean that the effects of disasters are more acutely felt by vulnerable, low income groups within a community affected by a natural disaster (Kulkarni, Bell, Beausoleil, Lein, Angel, & Mason, 2008).…”
Section: Insert Table 5 Herementioning
confidence: 99%
See 1 more Smart Citation
“…Despite frequent disasters, the research on disaster survivors’ psychological status and its associated factors in China is still thin. Given that psychological status and its associated factors such as resilience and other coping strategies of disaster survivors are likely to be influenced by social and cultural contexts (Gunnestad, ; Ibañez, Buck, Khatchikian, & Norris, ; Liu & Mishna, ), more research is critical to develop evidence‐based interventions to work with disaster survivors in China.…”
Section: Introductionmentioning
confidence: 99%